Astronomical technology - the past and the future: Karl Schwarzschild Award Lecture 2015 - Appenzeller, Immo (Astronomische Nachrichten, 2016)
The past fifty years have been an epoch of impressive progress in the field of astronomical technology. Practically all the technical tools, which we use today, have been developed during that time span. While the first half of this period has been dominated by advances in the detector technologies, during the past two decades innovative telescope concepts have been developed for practically all wavelength ranges where astronomical observations are possible. Further important advances can be expected in the next few decades. Based on the experience of the past, some of the main sources of technological progress can be identified. (© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Gesehen am 18.08.2020